THE INFLUENCE OF PSYCHOSOCIAL FACTORS AT WORK ON THE EMPLOYEE PERFORMANCE (Journal of Business and Management, 2021)
Employees are the vital aspect in supporting the business with duties and responsibilities in developing business. However, one of the things that are often forgotten by the workplace is the importance of maintaining psychosocial conditions, such as letting them work like machines with excessive workloads and with various pressures to achieve business goals in the workplace. We first identify the psychosocial conditions experienced by employees at work using the short version of COPSOQ III. In this instrument, there are six domains with 23 factors. Meanwhile, employee performance is measured by the concept of Robbins (2006), which has indicators of quality, quantity, effectiveness, work commitment, punctuality, and independence. This research uses a quantitative method with 181 respondents taken randomly from Indonesian employees who work in a company or an agency. This study confirmed that all psychosocial domains had a significant influence (p < 0.05) on employee performance, and 16 factors contained in these domains directly correlated to performance. These findings suggested the business community and workplace pay attention to these six domains or, more specifically, to the 16 correlated factors because influences give to employee performance.Keywords: psychosocial, employees, COPSOQ III, employee performance